Numerical simulation of dust cake build-up and detachment on rigid ceramic filters for high temperature gas cleaning - T. G., Chuah; J. P. K., Seville (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/